Operating systems in depth - Doeppner, Thomas W. (Wiley, 2011)
"Programmers don't want to just read about the core concepts of operating systems. They want to learn how to apply the material by actually building applications. This new book motivates them by presenting numerous programming exercises at the code level. They are not only introduced to the OS concepts and abstractions, but also the implementation. Two design projects are integrated throughout the book that they'll be able to follow to get them into the code. Self-assessment and review material is presented at the end of each chapter to reinforce concepts. These features help to make this an excellent resource for programmers to gain invaluable experience."--